2016
DOI: 10.3390/v8070180
|View full text |Cite
|
Sign up to set email alerts
|

Who Regulates Whom? An Overview of RNA Granules and Viral Infections

Abstract: After viral infection, host cells respond by mounting an anti-viral stress response in order to create a hostile atmosphere for viral replication, leading to the shut-off of mRNA translation (protein synthesis) and the assembly of RNA granules. Two of these RNA granules have been well characterized in yeast and mammalian cells, stress granules (SGs), which are translationally silent sites of RNA triage and processing bodies (PBs), which are involved in mRNA degradation. This review discusses the role of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(111 citation statements)
references
References 271 publications
1
100
0
Order By: Relevance
“…To overcome host translation shutoff, several RNA viruses evolved different strategies, including mechanisms that interfere with SG formation (8, 9). It has been reported that DENV inhibits SG formation in baby hamster kidney (BHK-21) cells by sequestering the SG-initiating proteins T cell internal antigen-1 (TIA-1) and TIA-1-related protein R (TIAR) on the 3′ untranslated region (UTR) of its RNA genome (36), although we found previously that infection of Huh7 cells with DENV induced few sporadically oscillating SGs (56).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome host translation shutoff, several RNA viruses evolved different strategies, including mechanisms that interfere with SG formation (8, 9). It has been reported that DENV inhibits SG formation in baby hamster kidney (BHK-21) cells by sequestering the SG-initiating proteins T cell internal antigen-1 (TIA-1) and TIA-1-related protein R (TIAR) on the 3′ untranslated region (UTR) of its RNA genome (36), although we found previously that infection of Huh7 cells with DENV induced few sporadically oscillating SGs (56).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of protein synthesis is tightly linked to the assembly of stress granules (SGs), which are cytosolic aggregates of stalled translation preinitiation complexes (57). As they require an intact translation machinery to translate their viral genome, several viruses antagonize SG formation during infection, although some may also exploit SG responses for their replication (8, 9). …”
Section: Introductionmentioning
confidence: 99%
“…Viruses of many classes can modulate SG formation and impact virus infections (33,34). The mechanisms that underlie this process and the effects that it has on the host to facilitate infection are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the best‐characterized RNA granules in the cytosol of somatic cells are processing bodies (P‐bodies) and stress granules (SGs), both typically encompassing mRNPs not engaged in translation . Such RNA granules are emerging as key control elements of messenger RNA (mRNA) metabolism and their deregulation has been linked to various human pathogenic conditions including cancer, degenerative disorders and viral infections …”
Section: Introductionmentioning
confidence: 99%